2012
DOI: 10.1371/journal.pone.0040112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gene, Protein and Neurotrophin Expression in the Brain of Mice Exposed to Space Environment for 91 Days

Abstract: Effects of 3-month exposure to microgravity environment on the expression of genes and proteins in mouse brain were studied. Moreover, responses of neurobiological parameters, nerve growth factor (NGF) and brain derived neurotrophic factor (BDNF), were also evaluated in the cerebellum, hippocampus, cortex, and adrenal glands. Spaceflight-related changes in gene and protein expression were observed. Biological processes of the up-regulated genes were related to the immune response, metabolic process, and/or inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 50 publications
(62 reference statements)
2
37
0
2
Order By: Relevance
“…Recently, a payload for rodents, named Mice Drawer System (MDS) was built to house mice aboard the International Space Station (ISS) for investigating the long-term adaptation to space conditions [31]. It was reported that the expression of neuron growth factor (NGF) and brain-derived neurotrophic factor (BDNF) was reduced in brain regions such as the cortex and the hippocampus of spaceflown animals as compared to ground control ones [32]. The same study revealed that genes involved in long-term potentiation, axon guidance, neuronal growth, cone collapse, cell migration, dendrite branching and dendritic-spine morphology were up-regulated in the whole brain of mice exposed for 91 days to the ISS environment [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a payload for rodents, named Mice Drawer System (MDS) was built to house mice aboard the International Space Station (ISS) for investigating the long-term adaptation to space conditions [31]. It was reported that the expression of neuron growth factor (NGF) and brain-derived neurotrophic factor (BDNF) was reduced in brain regions such as the cortex and the hippocampus of spaceflown animals as compared to ground control ones [32]. The same study revealed that genes involved in long-term potentiation, axon guidance, neuronal growth, cone collapse, cell migration, dendrite branching and dendritic-spine morphology were up-regulated in the whole brain of mice exposed for 91 days to the ISS environment [32].…”
Section: Introductionmentioning
confidence: 99%
“…As previously described, gene expression is reported to be altered by the microgravity environment in space (Honda et al, 2012;Santucci et al, 2012;Blaber et al, 2013). Considering the alteration in gene expression associated with the chromatin conformation, further investigations are required to determine whether the chromatin structure is actually changed by microgravity.…”
Section: Chromatin Structure (Gravity Sensing)mentioning
confidence: 85%
“…Indeed, proteomics analysis is now frequently used in space studies including the ground-based study such as NASA human research program, radiobiology program, as described above. For example, gene expression is analysed in the recent space studies indicating its alteration by the microgravity environment in space (Honda et al, 2012;Santucci et al, 2012;Blaber et al, 2013). In these studies, such proteomics technologies were applied for studying lifespan control in C. elegans (Honda et al, 2012), evaluation of protein in the brain of mice (Santucci et al, 2012) and the mechanisms on bone loss in mice (Blaber et al, 2013).…”
Section: Gene Expression (Cellular Response)mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in mice [30][31][32] suggest attenuation of neurotrophic factors associated with neurotransmission, it remains unclear how these changes may affect alteration in behavior and how such changes may translate into humans. It is essential to develop a deeper understanding on the potential for attenuation of brain function given the striking effect of spaceflight on structural plasticity and changes in grey matter volume [33], some of which may be attributable to fluid shifts.…”
Section: Brain Functionmentioning
confidence: 99%